Lean Six Sigma implementation in East Africa: findings from a pilot study. Issue 6 (12th October 2015) - Douglas, Alexander; Douglas, Jacqueline; Ochieng, Jacqueline
Abstract : Purpose: – This paper reports the results of a pilot study on the implementation of Lean Six Sigma (LSS) in East African service and manufacturing organizations. The purpose of this paper is to determine the critical success factors for implementation of such a strategy as well as any barriers. A further aim was to determine the knowledge, usage and usefulness of LSS tools and techniques within those organizations. Design/methodology/approach: – A quantitative approach was taken utilizing a survey questionnaire which was sent to a sample of organization employees who had attended Yellow, Green or Black Belt LSS training courses organized by the Kenya Institute of Management in Nairobi. Employees attending such courses came from Kenya, Uganda, Tanzania and Rwanda. Findings: – Results indicate that the most useful tools are most of the original seven tools of quality improvement proposed by Ishikawa over 50 years ago and the most important factor for successful implementation of LSS is management involvement and participation. Research limitations/implications: – The main limitation is that this is a pilot study so to confirm the findings a full survey of East African organization needs to be undertaken. Practical implications: – The findings have implications for trainers, consultants and practitioners with regards to the implementation of LSS within organizations as well as the focus of the content of LSS training courses. Originality/value: – This paper reports the first study on the implementation of LSS in East Africa and will be of value to practitioners, trainers, consultants and researchers of LSS in East Africa and beyond.